Pengaruh Kedisiplinan, Motivasi Kerja, dan Komitmen Organisasi terhadap Kepuasan Kerja Karyawan - Mamik (Universitas Brawijaya, Indonesia, 2009)
As a one of big industry that have contribution for Indonesian economy, the growth of Indonesian's paper industry in 3 years later always declines. Especially, there are 3 paper industries at East Java that have international market orientation. Because of the big size of employee, the research and development of the quality of human resources is urgent to be done. The purposes of this study are analyze and examine the influence of discipline, work motivation, and organizational commitment upon the employee job satisfaction in paper industries at East Java. The population in this study are 5.021 operational employees in 3 paper industries at East Java. Data collecting was obtained by field observation, distributing the questionnaire and interviewing to 100 employees as sample. Then, data was processed and analyzed by using multiple linier regression analysis, with SPSS version 13.0. The results of this study are: (1) discipline has significant influence upon the job satisfaction; (2) work motivation has significant influence upon the job satisfaction; (3) organizational commitment has significant influence upon the job satisfaction.